2017
DOI: 10.5603/fhc.a2017.0006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen concentration on T cell proliferation and susceptibility to apoptosis in healthy men and women

Abstract: Introduction.Much of what we know about the functioning of human T lymphocytes is based on the experiments carried out at atmospheric oxygen (O 2 ) concentrations, which are significantly higher than those maintained in blood. Interestingly, the gender differences in the activity of T cells and their susceptibility to apoptosis under different O 2 conditions have not yet been described. The aim of the study was to compare two main markers of lymphocyte function: proliferation capacity and ability to produce cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…This may be linked with estrogen-sensitive PPARγ/dependent differentiation of Tfh cells 59 . A more prominent increase in the number of Tfh cells in female rat dLNs following immunization with CII leading to sex bias in their number in immunized rats (greater number in females) was consistent with data indicating that Th cells from adult women and female mice have greater proliferative capacity than those from age-matched men and male mice, respectively 60,61 . Additionally, we have recently shown the greater activation/proliferation of Th cells from dLNs of female CII-immunized DA rats compared with their male counterparts 10 .…”
Section: Discussionsupporting
confidence: 87%
“…This may be linked with estrogen-sensitive PPARγ/dependent differentiation of Tfh cells 59 . A more prominent increase in the number of Tfh cells in female rat dLNs following immunization with CII leading to sex bias in their number in immunized rats (greater number in females) was consistent with data indicating that Th cells from adult women and female mice have greater proliferative capacity than those from age-matched men and male mice, respectively 60,61 . Additionally, we have recently shown the greater activation/proliferation of Th cells from dLNs of female CII-immunized DA rats compared with their male counterparts 10 .…”
Section: Discussionsupporting
confidence: 87%
“…A recent study revealed that breathing 60% O 2 increased activities of T and NK cells, and decreased immunosuppressive molecules in a murine lung cancer model (Hatfield et al, 2015). Some researchers have also demonstrated that lymphocytes have higher proliferation efficiency in conditions of rich O 2 compared with hypoxia (Waskowska et al, 2017;Atkuri et al, 2005b). Accordingly, it is tempting to speculate that sufficient O 2 may improve the antiviral ability of patients with early COVID-19 by increasing the abundance and activities of immune cells.…”
Section: Oxygen Supplementation Can Improve Antiviral Immune Responsementioning
confidence: 99%